Estresse no trabalho e alto risco cardiovascular em funcionários do campus saúde de uma universidade pública - Helena Chaves Xavier (2015)
Cardiovascular Diseases (CVD) stand out as the leading causes of death worldwide, accounting for the most significant public health problem today. In recent decades, many studies have been made to identify the factors that increase the risk of CVD occurrence. However, these determinants were not also consistently investigated, yet, for the Brazilian population. This is an epidemiological, cross-sectional analytical study, conducted with the aim of analyzing the factors associated with high cardiovascular risk in employees of health campus of a Public University. The sample consisted of 211 participants, of both sexes, aged between 20 and 65 years, whose demographic, socioeconomic, anthropometric, biochemical and blood pressure analyzes, lifestyle and work conditions data were collected. Cardiovascular risk was calculated using the Framingham score. It were done statistical analysis descriptive (absolute and relative frequencies), bivariate (chi-square test of Pearson and Fisher's exact test) and multivariate analysis (Poisson regression) with significance level of 5%. The prevalence of high cardiovascular risk was 28% (95% CI: 20.0 to 34.5). The anthropometric, biochemical, nutritional and lifestyle profiles of workers were very poor, with high prevalence of global obesity, dyslipidemia, hypertension, inadequate dietary habits, alcohol consumption and sedentary lifestyle. Control demand [job strain category (PR: 4.12, 95% CI: 1.56 to 10.84), body mass index [25-29.9 (PR: 2.11, 95% CI: 1.08 to 4.15) and 30 (PR: 3.33, 95% CI 1.77 to 6.26) and social support [high support category (PR: 1.68, 95% CI: 1.12 to 2.53)] were independently associated with high cardiovascular risk. It is important that these findings are considered in discussions on promoting worker health, aiming to establish measures for prevention, control and treatment of CVD in this population and consequently decrease of chronic non-communicable diseases, emphasizing, especially, on creating work environments favorable to health.